Three dimensional analysis of natural convection and entropy generation in a sharp edged finned cavity - Kolsi, Lioua; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Alghamdi, Abdulaziz; Borjini, M. Naceur (Elsevier Science Inc, 2016)
A computational study has been performed to make a computational analysis of natural convection and entropy generation in a sharp edged finned cavity. Three dimensional analysis has been done by solving governing equations with a written computational code in Fortran. The study is performed for fin inclination angles from -60 degrees to 60 degrees, Ra= 10(5), Pr= 0.7, R-c (conductivities ratio) changes from 0.01 to 100 and irreversibility coefficient is taken as phi = 10(-5). It is observed that higher values of thermal conductivity ratio (Rc >= 1) do not affect entropy generation due to heat transfer and Bejan number. (C) 2016 Faculty of Engineering, Alexandria University. Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Entropy generation; Inclined fin; Natural convection; Three dimensional